Takayasu Arteritis : Diagnostic Approach - Malikul Chair; Bambang Setyohadi; RM Suryo Anggoro; Anna Ariane (Indonesian Rheumatology Association, 2018)
Takayasu arteritis (TA) is a systemic, inflammatory large-vessel vasculitis of unknown etiology that most commonly affects women of childbearing age. It involves the aorta and its major branches. The main abnormalities found in this disease are vascular ischemic signs/symptoms including claudication, carotid bruit, weak distal pulsation. Hereby we report a case a 25-year-old unmarried female complained a recurrent left arm pain, worsening when she did her work as a doctor. Formerly, she had experienced intermittent bilateral leg pain for four years with strange sound coming from inside her neck. She was hospitalized half a year ago due to acute limb ischemic and she was diagnosed with TA after the imaging showed multiple stenosis in large arteries including bilateral neck area, shoulder area, abdominal aorta, and right renal artery. The inferior right extremity biopsy showed the histologist result of erythema nodosum appearance. Cuantitative C reactive protein (CRP): 19,8, erythrocyte sedimen rate (ESR): 53. The others laboratory data to exclude differential diagnosis are unremarkable. This report demonstrates the importance of diagnostic approach in rare case of Takayasu’s arteritis patients. Keyword: Diagnostic; Vasculitis, Takayasu Arteritis